Prevalence and risk factors of depressive symptoms among institutionalized elderly in Sabah, Malaysia Borneo - Helmy Sajali; Syed Sharizman Syed Abdul Rahim; Afidah Abidin; Premala Subramaniam; Mohd Fazeli Sazali; Mohammad Saffree Jeffree; Mazlinda Musa; Nicholas Tze Ping Pang; Azizan Omar; Mohd Faizal Madrim; Khalid Mokti; Abdul Rahman Ramdzan; et al. (Malaysian Public Health Physicians Association, 2021)
The elderly population in Malaysia are multiplying, and older people's reliance on social services such as the elderly institutions has increased. Mental health problems especially depression is one of the main problems with institutionalized elderly. This study aims to determine the prevalence and associated risk factors of depression among elderly in all three state-run institutions in Sabah. A multi-centered, cross-sectional study was conducted on residents of all three state-run elderly institutions in Sabah (N=110). All residents that fulfill the criteria were included in the study through a self-administered set of validated questionnaires that measure perceived social support, loneliness, and depression. Statistical Package for the Social Sciences by IBM (IBM SPSS) v25 was used and Chi Square and logistic regression for analysis. The prevalence of depressive symptoms is at 60.9%. The independent risk factors for depression in residents were male gender (OR=4.09, 95%CI=1.55, 10.79), perceived poor health status (OR=6.63, 95%CI=2.49, 17.65), and loneliness (OR=6.12, 95%CI=2.02, 18.53). Depression is prevalent among the elderly in the state-run institutions in Sabah, Malaysia. A comprehensive mental health screening program needs to be implemented for the elderly institutions along with adequate training for staff to handle mental health issues in the elderly